Nutritional status and protein quality of diets of selected vegetarian and non-vegetarian children aged 2 to 6 years - Aguilar, Lourdes Vargas
Vegetarianism has gained popularity among some Filipinos for various reasons such as health and nutrition, religion and politics, or ethical and metaphysical considerations. Because the protein quality of plant foods is generally lower than that of animal foods, questions arise concerning the use of the former as meat substitutes without sacrificing good nutrition, particularly in preschoolers who are most vulnerable to the effects of malnutrition. This study was undertaken to study the nutritional status and protein quality of diets of vegetarian preschoolers compared with non-vegetarians of similar ages. 18 pairs of children with ages ranging from 2 to 6 years, living in different areas in Metro Manila (Pasay City, Baesa, Caloocan City, San Juan and Paranaque) were matched for age and place of residence. 1 member of each pair had been on a vegetarian diet since birth and was assigned to the experimental group while the other was a non-vegetarian and was assigned to the control group. Socio-demographic characteristics (family income, food expenses, employment status, educational level of parents), anthropometric measurements (weight, height and circumferences of head, chest and mid-upper arm) and nutrient intakes (energy, protein, iron and vitamin A) of both groups of subjects were taken, assessed and compared statistically. The findings indicated that the experimental and control subjects were comparable in terms of per capita income, food expenses, employment status of parents, and educational level of mothers. Most of the subjects had satisfactory nutritional status in terms of anthropometric measurements and dietary intakes. As a group, the non-vegetarians had slightly higher values for weight, head, chest and mid-upper arm circumferences than the vegetarians but the differences were not statistically significant. The non-vegetarian had better intakes of energy and protein than the vegetarians, and the reverse was true for iron and Vitamin A. However, the differences in the adequacies of the 4 nutrients were not statistically significant. In the assessment of protein quality, both vegetarian and non-vegetarian diets had satisfactory mean of NDPE , although as a whole the latter was significantly higher. The most limiting amino acids in the vegetarian diets were menthionine and cystine while in the non-vegetarian diets it was threonine. At the levels of protein intakes found among the subjects (i.e., more than adequate) statistical exploration through correlation-regression analysis did not show any association between nutritional status and the protein quality of diets.